Understanding English speaking practice in public schools in Kazakhstan: a case study in Almaty - Tuspekova, Almagul; Rosniah Mustaffa,; Kemboja Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Teaching and learning of English as a spoken language in English as a Foreign Language (EFL) still remains a major concern in Asian context as evident from recent studies. The situation is similar in Central Asian classrooms where it received little attention. Specifically, this study investigates a classroom in a local public school in Kazakhstan through the lens of a teacher and the students during speaking activities. A case study qualitative approach was employed using interviews, classroom observations, and document analysis as data collection methods. In total, 21 individual interviews and 30 hours of classroom observations were conducted and recorded. Analyses and interpretations of data show that firstly the speaking activities lack in negotiation of meaning as they are predominantly aimed at predetermined monological performance-based speech. Secondly, out-of-school learning was prevalent among the majority of students at private learning centres. Also, self-learning at home was practiced by male students via interacting with foreign players in online video games and by female students via watching English movies. Thirdly, classroom interactions were accountable in facilitating and inhibiting the practice of speaking. Finally, there was a mismatch between the perceptions of the teacher and the students on the challenges of the speaking practice. The teacher indicated insufficient teaching hours and students’ limited background knowledge, while the students emphasised the teacher’s unwillingness to use English as a language of instruction and to practice impromptu speech in class. In summary, the findings highlight some of the apprehensions faced by the teacher and the students which reveals the current English speaking practice in Kazakhstani classroom.